FINANCIAL STATEMENT FRAUD USING REVISED BENEISH M-SCORE MODEL: EVIDENCE IN BANKING INDONESIA - Pupung Purnamasari (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2023)
The purpose of this research is to determine the extent of the possibility of fraud in the banking sector in Indonesia. This study involves banks that have gone public on the IDX from 2017 to 2021. This study uses the Beneish model to classify banks as fraudulent and non-fraud. Then, the probit regression model is applied based on the results of the Beneish model to reclassify a bank as fraud or vice versa. The study revealed that the number of banks that were detected as experiencing the possibility of fraud was 41 banks for 5 years using the Beneish M-Score model approach. Then the results of testing using the Beneish M-Score which has been revised according to the characteristics of the banking itself are as many as 56 banks which have indicated that they have experienced fraud for 5 years. This study contributes to the fraud literature by providing evidence that fraud is widespread in the banking sector in Indonesia even though banks have strict regulations